PERANCANGAN SENTRA USAHA MIKRO, KECIL, MENENGAH (UMKM) KHAS KALIMANTAN TENGAH DI KOTA PALANGKA RAYA - SYANATA, RIFQI; Hamidah, Noor (Jurusan Arsitektur UPR, 2025)
Palangka Raya, as the provincial capital and center of government, has a strategic position in supporting Central Kalimantan's economic growth. The economic sector in Palangka Raya City is supported by Micro, Small and Medium Enterprises (MSMEs) operating in the fields of trade, culinary, handicrafts and services, which rely on local resources and unique local wisdom from the indigenous Dayak Ngaju tribe community. Adequate economic centers in Palangka Raya City, such as traditional markets and modern shopping centers, also contribute to the dynamics of MSMEs in Palangka Raya apart from Dekranasda. Many small businesses use traditional markets as the main place to market their products. However, challenges such as competition with products from outside the region and lack of product standardization often become obstacles for local MSME players. MSME centers in Palangka Raya City have great opportunities to continue to develop. The Palangka Raya City Government realizes the importance of supporting the growth of MSMEs as part of its regional economic development strategy. Various programs have been launched, both by the Department of Cooperatives and MSMEs and other related agencies, to strengthen the capacity and competitiveness of MSME players. The research aims to formulate an adaptive Indonesian architectural concept for the MSME Center in Palangka Raya City. The research method uses qualitative methods through literature studies, comparative studies based on survey and interview data, as well as precedent studies to study archipelago architectural approaches. The Indonesian architectural approach pays attention to aspects of sustainability, local wisdom and flexibility in its use. The proposed design concept combines traditional elements such as roofs, natural ventilation and the use of local materials with modern technology to increase energy efficiency and user comfort. It is hoped that this research can contribute to the development of sustainable and culturally valuable MSME center designs in Indonesia.